Evaluasi Tanah Pasir Lepas Terhadap Potensi Likuefaksi di Area Bandara Kulon Progo Berdasarkan Peta Gempa Indonesia tahun 2017 - Yuki Achmad Yakin; Desti Santi Pratiwi; Virhan Maulana Fachrezy (Fakultas Teknik, 2023)
Java Island is traversed by the Pacific Ring of Fire, making Java Island an earthquake-prone area. One of the problems caused by earthquake is the danger of liquefaction. Kulon Progo is in a zone of high liquefaction vulnerability. Liquefaction is the loss of soil shear strength due to changes in soil properties from solid to liquid caused by cyclic loads that occur so that the pore water pressure increases beyond the vertical stress and causes the effective stress to be zero. Liquefaction mostly occurred in sand loose and saturated condition. Peak Ground Acceleration values (PGA) and earthquake magnitude are sourced from Peta Gempa Indonesia 2017 and use soil data from the Standard Penetration Test (SPT) test results. In evaluating the potential for liquefaction at the study site, the analysis method Youd Idriss, Idriss Boulanger, and Tokimatsu Yoshimi was used. The results of the comparison between soil resistance or Cyclic Resistance Ratio (CRR) with cyclic loads that occur or Cyclic Stress Ratio (CSR) show the same results. In part 1 it can be seen that the average depth of liquefied soil starts from a depth of 1.7 – 4 meters or as deep as 2.3 m, while in part 2 it can be seen that the average depth of liquefied soil starts from a depth of 3.3 – 4 meters or as deep as 0.7m.